Impact of impaired kidney function on outcomes of Nigerians with COVID-9 infection: report of two cases from the University College Hospital, Ibadan (2021)
Covid-19 infection predominantly affects the respiratory system; however, other systems and organs are also affected. The kidneys are among the organs commonly affected by SARS-CoV-2 and this has been reported to be a predictor of increased severity, need for intensive care (ICU), admission, and death. We presented two cases of COVID-19 that were associated with co-morbidities that include diabetes mellitus, systemic hypertension and impaired kidney function. The relationship of the multiple co-morbidities particularly the impaired kidney function with the outcomes of COVID-19 infection and the challenges of offering dialysis for patients with COVID-19 infection with kidney failure were discussed. The two cases presented also highlighted the state of preparedness for the management of COVID-19 and its various complications and co-morbidities, particularly kidney failure in a tertiary hospital in Nigeria at onset of the COVID-19 outbreak. WAJM 2021; 38(3): 292–296.